Using unsupervised machine learning to characterize recovery patterns in elite canoe-kayak athletes across the Olympic training year - Foucaud, A.; Durand, F.; Meric, H. (Frontiers in Sports and Active Living, 2025)
Background: Continuous wearable monitoring generates high-volume data, yet methods to translate these streams into actionable recovery insights for elite athletes remain scarce. This study applied a multi-layer, unsupervised machine-learning pipeline to characterize nightly recovery states and season-long physiological phenotypes In Olympic-level French canoe-kayak paddlers.